Larval food supply constrains female reproductive schedules in Hippodamia convergens (Coleoptera: Coccinellidae) - Vargas, German; Michaud, J. P.; Nechols, James R. (My University, 2013)
Reproductive schedules are a critical aspect of life history intrinsically linked to a species' ecology. We explored dynamic trajectories of daily fecundity, egg size, and egg fertility in three size classes of Hippodamia convergens Guerin-Meneville produced by varying larval access to food, eggs of Ephestia kuehniella Zeller. Adult pairs were held with ad libitum food and eggs were collected daily, counted, and a subsample measured. Egg fertility declined steeply over 25 clutches in small females, gradually in large females, but remained relatively stable in medium females. In small females, egg size and daily fecundity declined in a linear manner. There was no clear indication of an egg size-number tradeoff. In medium females, both egg size and daily fecundity peaked around the 16th day of oviposition, after which both declined. Large females began oviposition earlier and achieved peak egg size about day 7, and peak fecundity around day 12. Large females thus expressed a larger proportion of their reproductive effort early in adult life, a strategy inferred to be adaptive in the context of aphidophagy; a larger proportion of progeny would develop early in the exponential growth phase of the prey population when food is most abundant. Increases in egg size during this period may improve the survival of later-developing progeny; prey become scarce as aphid outbreaks decline and competition intensifies, favoring offspring with a larger body size at eclosion. Larval diet restriction appeared to constrain these presumably adaptive changes in egg size and daily fecundity, largely through effects on maternal body size.
Citation: Vargas, German, J. P. Michaud, and James R. Nechols. 2012. “Larval Food Supply Constrains Female Reproductive Schedules in Hippodamia Convergens (Coleoptera: Coccinellidae).” Annals of the Entomological Society of America 105 (6): 832–39. https://doi.org/10.1603/AN12010.
Keywords: Aphidophagy; Egg size; Fecundity; Maternal effect; Reproductive effort